THE EFFECTIVENESS OF THE CIRC LEARNING MODEL ASSISTED BY TPACK-BASED E-LKPD ON THE JUNIOR HIGH SCHOOL STUDENTS' NUMERACY LITERACY SKILLS - Rafa' Syadza Ramadhani; Yesi Franita; Megita Dwi Pamungkas (JME (Journal of Mathematics Education), 2026)
Numeracy literacy is one of the important competencies of the 21st century, but the numeracy literacy skills of students in Indonesia are still relatively low. This study aims to analyze the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) learning model assisted by E-LKPD based on Technological Pedagogical Content Knowledge (TPACK) on the numeracy literacy skills of junior high school students. This study uses a quasi-experimental method with a nonequivalent pretest-posttest control group design. The research sample consisted of 28 seventh-grade students from class VII E as the experimental group and 25 seventh-grade students from class VII H as the control group at SMP Negeri 1 Mungkid. Data were collected using numeracy literacy ability tests and analyzed through Paired Sample t-Test, Independent Sample t-Test, N-Gain, and Cohen’s d effect size. The research results show that the numeracy literacy skills of students in the experimental class and the control class experienced a significant improvement after the learning process. In addition, there is a significant difference between the numeracy literacy abilities of students in the experimental class and the control class after the treatment was given (p=0.021). Although the N-Gain values of both groups are still in the low category, the experimental class achieved a higher improvement compared to the control class. Cohen’s d effect size analysis shows that the CIRC model assisted by TPACK-based E-LKPD has a significant impact on students' numeracy literacy skills. These findings indicate that the integration of the CIRC model with TPACK-based E-LKPD can be an effective learning alternative to support the development of students' numeracy literacy in mathematics education.